PENGARUH BAGI HASIL DAN BONUS (RETURN) TERHADAP DANA PIHAK KETIGA DENGAN BI 7-DAY (REVERSE) REPO RATE SEBAGAI VARIABEL MODERATING - Nadya Ulfah; M. Ridwan Ridwan; Nurul Jannah (Fakultas Ekonomi Bisnis Islam, 2023)
The key to the success of a bank in carrying out its functions is the bank that carries out a management in managing funds. Public funds or third party funds kept in banks are the largest sources of funds that banks rely on the most and consist of 3 types, namely demand deposits, deposits and savings. Apart from Third Party Funds (DPK), banking economic growth is influenced by interest rates. Therefore, this study aims to determine the effect of profit sharing and bonuses (return) on third party funds, to determine the effect of the BI 7-Day (Reverse) Repo Rate as a moderating variable, and to determine the effect of profit sharing and bonuses (return) and BI 7-Day (Reverse) Repo Rate as a moderating variable for third party funds at PT. Bank Syariah Indonesia for the 2016-2021 period. The research that the writer uses is a research with a quantitative approach. The data analysis technique used in this study is to use simple linear regression analysis with hypothesis testing, namely the coefficient of determination, T test and F test. Before using simple regression analysis, the classical assumption test is performed first which includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Based on the results of the moderated regression analysis test which shows that profit sharing and bonuses (return) have an effect on third party funds. In addition, the BI 7-Day (Reverse) Repo Rate is also able to moderate profit sharing and bonuses (return) with third party funds. Which means the BI 7-Day (Reverse) Repo Rate strengthens the relationship between profit sharing and bonuses (return) with third party funds.